A Defense-in-depth Cybersecurity for Smart Substations - M. N. Dazahra; F. Elmariami; A. Belfqih; J. Boukherouaa (Institute of Advanced Engineering and Science, 2018)
The increase of cyber-attacks on industrial and power systems in the recent years make the cybersecurity of supervisory control and data acquisition and substation automation systemsa high important engineering issue. This paper proposes a defense in depth cybersecurity solution for smart substations in different layers of the substation automation system. In fact, it presents possible vulnerabilities in the substation automation system and propose a multiple layer solution based on best practice in cyber security such as the hardening ofdevices, whitelisting, network configuration, network segmentation, role-based account management and cyber security management and deployement.